2011
DOI: 10.1901/jaba.2011.44-793
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Efficiency of and Child Preference for Forward and Backward Chaining

Abstract: Comparative studies of forward and backward chaining have led some to suggest that sensitivity to each teaching procedure may be idiosyncratic across learners and tasks. The purposes of the current study were threefold. First, we assessed differential sensitivity to each chaining procedure within children when presented with multiple learning tasks of similar content but different complexity. Second, we evaluated whether differential sensitivity to a chaining procedure during a brief task predicted differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Furthermore, this approach may be effective as imagery, similar to physical skills, can be broken down into more manageable chunks and improved with practice (Hall, 2001;Williams et al, 2013). For example, children are able to learn a skill quicker through breaking it down, or "chaining" (Slocum & Tiger, 2011). A similar approach was undertaken with the present imagery intervention.…”
Section: Layering Pettlep Elements and Imagery Abilitymentioning
confidence: 95%
“…Furthermore, this approach may be effective as imagery, similar to physical skills, can be broken down into more manageable chunks and improved with practice (Hall, 2001;Williams et al, 2013). For example, children are able to learn a skill quicker through breaking it down, or "chaining" (Slocum & Tiger, 2011). A similar approach was undertaken with the present imagery intervention.…”
Section: Layering Pettlep Elements and Imagery Abilitymentioning
confidence: 95%
“…The parent's high-preference (HP) prompting procedure was identified once the parent selected one procedure six more times than any other procedure (Slocum & Tiger, 2011). Sessions continued until we identified the HP procedure, or the parent completed 20 choice sessions with no preference (Luczynski & Hanley, 2009).…”
Section: Choice Sessionsmentioning
confidence: 99%
“…Chaining is an effective method that falls under applied behavioral analysis teclmiques (Hayward et ai., 2009). Slocum and Tiger (2011) completed a study of backwards and forwards chaining with children with developmental and leaming disabilities. TIns study identified that both backwards and forwards chaining were successful with children, though one was no more successful then the other.…”
Section: Cognitive Behavioral Theorymentioning
confidence: 99%